The use of directive speech transfer patterns as an implementation of teacher interaction styles in Indonesian language learning - Mujianto, Gigit; Setiawan, Arif; Melati, Inka Krisma; Oo, Cherry Zin (Universitas Ahmad Dahlan, 2025)
The application of the teacher's interaction style by arranging speech with directive speech is a superior ability in Indonesian language learning. This is because teachers are required to implement Indonesian learning that can develop critical, creative, communicative, and collaborative characters in students. Therefore, this study aims to describe speech switching through how to take over the turn of speech and provide a turn of speech with directive speech as a form of applying the teacher's interaction style in Indonesian learning to increase students' active participation in developing critical, creative, communicative, and collaborative skills. The approach used in this study is the classroom discourse approach. This class discourse approach directs analysis on data obtained from formal and planned conversation interactions (plan discourse). The focus of this conversation interaction lies with the teacher, as the determinant of the topic of conversation. The three main things appear in this Indonesian learning research in the form of: (1) students give honest responses to learning stimulants provided by teachers, (2) students submit more opinions on the information conveyed by the teacher or on the opinions submitted by other students, provide more information, (3) students make their own learning conclusions in their own language and way, Both individually and in groups, (4) students make optimal use of their activities, respond to learning stimuli provided by teachers, (5) students who ask questions, both to teachers and to other students, and (6) students make their own assessments of the results of their work.